M1 resonance in sd-shell nuclei - Kachan, A.S. (Вопросы атомной науки и техники, 2003)
γ-Decay of a resonance-like structure observed in the reactions of radiative capture of protons by ²¹Ne, ²²Ne, ²⁵Mg, ²⁶Mg, ²⁹Si, ⁰³Si, ³³S, ³⁴S, and ³⁶S nuclei is studied. The M1 resonance built on the ground state of ²²Na, ²³Na, ²⁶Al, ²⁷Al, ³⁰P, ³¹P, ³⁵Cl, and ³⁷Cl is identified. The position of the M1 resonance is explained taking into account pairing forces. Вивчено гама-розпад резонансноподібных структур, які спостерігаються в реакціїї радіаційного захвату протонів ядрами ²¹Ne, ²²Ne, ²⁵Mg, ²⁶Mg, ²⁹Si, ⁰³Si, ³³S, ³⁴S і ³⁶S. Ідентифіковано М1-резонанс на основних станах ядер ²²Na, ²³Na, ²⁶Al, ²⁷Al, ³⁰P, ³¹P, ³⁵Cl і ³⁷Cl. Виявлено, що на положення центра ваги М1-резонансу впливає величина np-, nn-, pp-спарювання. Изучен гамма-распад резонансноподобных структур, наблюдаемых в реакции радиационного захвата протонов ядрами ²¹Ne, ²²Ne, ²⁵Mg, ²⁶Mg, ²⁹Si, ⁰³Si, ³³S, ³⁴S, и ³⁶S. Идентифицирован М1-резонанс на основных состояниях ядер ²²Na, ²³Na, ²⁶Al, ²⁷Al, ³⁰P, ³¹P, ³⁵Cl, и ³⁷Cl. Обнаружено, что на положение центра тяжести М1-резонанса влияет величина np-, nn-, pp-спаривания.